The Experiences of Women Regarding Sexuality and Embodiment Within a Canadian Evangelical Context: A Phenomenological Study - Payne, Melissa (Université Saint-Paul / Saint Paul University, 2021)
The experiences of women regarding sexuality and embodiment within a Canadian Evangelical context is an area of limited research and the issue that this study specifically explores. For centuries, God has been depicted through a predominantly masculine framework that has left women devoid of relating to the Divine in her woman-ness. It is important to note that the role of the feminine among the monotheistic God is scarcely mentioned in the discourse of religion. How women are meant to understand their sexuality and bodies within the religious dimension can feel insurmountable. The topic of women and their experiences of sexuality and embodiment within the phenomenon of Evangelicalism is an important one, as it explores an area of women’s experience that can, and often does, get overlooked. Women’s sexuality within the Evangelical church in a Canadian context remains a topic that is often not discussed, and as seen throughout this study’s findings, has remained silenced across generations. This study looks at the convergence of three areas of human experience: sexuality, embodiment and religious/spiritual experience within this specific church context. How women experience or have experienced this religious phenomenon impacts the way they experience themselves as sexual and embodied beings. The findings of this study revealed the need for a Narrative approach to therapy when working with specific issues around sexuality, embodiment and spirituality, and an understanding of the deconstruction and reconstruction process in one’s spirituality. It also revealed the importance of embodiment practices and the need for sexuality and sexual issues to be included during the intake assessment within a therapeutic context.
Keywords: Women; Evangelicalism; Embodiment; Spirituality; Therapeutic context; Church; Identity; Intergenerational dialogue; Integration; Disintegration; Sexuality